Dowry from the Perspective of Islamic Law and Local Culturehas Been Critical of Society Practices - Karmawan Karmawan; Teguh Prawiro (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The problem in the study of dowry lies in the tension between normative concepts in Islamic law that emphasize simplicity and justice, and local cultural practices that often view dowry as a symbol of social status and prestige. This difference raises the need to understand how sharia norms and cultural constructions are integrated into marriage practices. This study aims to analyze dowry from the perspective of Islamic law and local culture and explain the forms of interaction between the two in the context of contemporary society. The research method used is a qualitative approach with library research that combines juridical-normative and sociological approaches. Data are analyzed descriptively and analytically to examine the concept of dowry, cultural practices, and the social dynamics that influence its implementation. The analysis results show that dowry has multidimensional functions, namely as a legal obligation, a symbol of respect, and a socio-economic instrument. The integration between Islamic law and local culture can occur harmoniously as long as cultural practices do not conflict with sharia principles, such as justice, willingness, and welfare. However, in some cases, the dominance of cultural values ​​leads to a distortion of the meaning of dowry from its normative purpose. The contribution of this research is to offer an integrative understanding of dowry that places Islamic law and local culture within a complementary framework, making it relevant for the development of contemporary Islamic family law studies.